Health benefits and nutritional information of Asian Muslim halal food spices - Rahman, Md. Mokhlesur; Che Mohamad, Che Anuar; Mohamed, Awang (IIUM, 2016)
“Let food be thy medicine and medicine be thy food” was the famous quote from the renowned philosopher and physician, Hippocrates. That was a good 2500 years ago, but food as medicine has once more gained great health and commercial values. Many researchers have attempted to explain why hot spices are attractive and pleasant to be tasted. It is thought that the burning sensation is due to the pain that originated from the nerve endings on the tongue. This subsequently releases endorphins, the body’s natural painkillers, thus leading to pleasurable and even euphoric sensations. Herbs and spices have traditionally been used to treat diseases for thousands of years. The word spice comes from Latin species, meaning a commodity of value and distinction. During their long and fascinating history, spices have often been more valuable than gold or precious stones, and the trade of spices has been an extraordinarily influential factor in history. Flowers, leaves, roots, bark, seeds and bulbs (the simplest of natural ingredients) are used in endless combinations to produce an infinite variety of flavours: sweet, sharp, hot, sour, spicy, aromatic, tart, mild, fragrant or pungent. On top of being used as common food ingredients, spices and herbs have also been used as medicine and to some, were favoured over commercial drugs because of less risk of potential side effects. The most popular herbs and spices are probably those originally used by Indian Muslim which has also spread to almost every part of the world. They managed to add the flavour and nutrients to their dishes without fats or calories. This review will attempt to identify the common Asian Muslim Halal herbs and spices and their relation to health and nutritional benefits.